2016
DOI: 10.1002/cmdc.201600276
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Optimization of the First Highly Selective GLUT1 Inhibitor BAY‐876

Abstract: Despite the long‐known fact that the facilitative glucose transporter GLUT1 is one of the key players safeguarding the increase in glucose consumption of many tumor entities even under conditions of normal oxygen supply (known as the Warburg effect), only few endeavors have been undertaken to find a GLUT1‐selective small‐molecule inhibitor. Because other transporters of the GLUT1 family are involved in crucial processes, these transporters should not be addressed by such an inhibitor. A high‐throughput screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(175 citation statements)
references
References 48 publications
11
163
1
Order By: Relevance
“…Antisense RNA targeting GLUT5 has proved effective against two breast cancer cells lines expressing this transporter [53]. Small molecule inhibitors specific for GLUT1, including WZB117 which we have utilized in our studies, have been identified [54], as have inhibitors for other transporters such as GLUT5 [55]. These molecules offer the opportunity to selectively target specific transporters as part of single or combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense RNA targeting GLUT5 has proved effective against two breast cancer cells lines expressing this transporter [53]. Small molecule inhibitors specific for GLUT1, including WZB117 which we have utilized in our studies, have been identified [54], as have inhibitors for other transporters such as GLUT5 [55]. These molecules offer the opportunity to selectively target specific transporters as part of single or combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…BAY‐876 (IC 50 =2 n m , Figure , Table ) possesses a clear preference for GLUT‐1 over GLUT‐2, ‐3, and ‐4. It competitively inhibits GLUT‐1 (Table ) and shows good in vitro and in vivo properties . However, BAY‐876 did not inhibit the growth of the triple‐negative breast cancer cell lines BT549, MDA‐MB‐436, and HCC70 at 3 μ m as determined by live‐cell imaging (Table ) .…”
Section: Discovery Of the Most Potent Glut Inhibitorsmentioning
confidence: 99%
“…GLUTs exhibit a tissue‐specific distribution and selective expression in cancer . GLUT‐1 is expressed at high levels in most cancers, and GLUT‐3 is predominantly found in the brain, arguing for the development of GLUT‐1‐selective compounds . However, GLUT‐3 is also overexpressed in numerous additional cancer types (beyond glioblastoma that originates from nervous tissue) such as breast and endometrial cancer, head and neck tumors, colon cancer, pancreatic cancer, non‐small cell lung cancer and thyroid carcinomas .…”
Section: Glut Isoform Selectivity Profiles To Target Cancermentioning
confidence: 99%
“…Extensive efforts have been made to discover new inhibitors of GLUTs, particularly GLUT1, as leads for developing novel anticancer drugs . Although a number of GLUT inhibitors have been reported, including BAY‐876, a potent and isoform‐specific GLUT1 inhibitor, none has entered the clinic to date.…”
Section: Figurementioning
confidence: 99%